Analysis of electrokinetic properties of NiFe2O4 nanoparticles synthesized by DC thermal plasma route and its use in adsorption of humic substances. Issue 2 (June 2016) - Bhosale, S.V.; Bankar, D.N.; Bhoraskar, S.V.; Mathe, V.L.
Graphical abstract: Abstract: The paper reports the influence of electro-kinetic properties of nanoparticles of NiFe2 O4 on the adsorption of humic substances (HS); with an aim of understanding their adsorption behavior. Crystalline single phase magnetic nanoparticles of NiFe2 O4 are synthesized by gas phase condensation method using DC thermal plasma reactor. Due to the high temperature and steep temperature gradient this method helps in producing highly crystalline nanoparticles with sufficiently large number of surface states suitable for adsorption. These particles possessed high value of zeta potential, reducing their agglomeration and resulting into an enhanced adsorption capacity. However no significant influence of plasma parameters is observed on their zeta-potential and iso-electric values. The adsorption kinetics is studied and fitted to non-linear kinetic models and the best fit is observed for the pseudo first-order model. The analysis of adsorption isotherms suggests that the non-linear Langmuir model fits better as compared to Freundlich adsorption model. The adsorption of HS onto the nanoparticles is seen to depend on the pH value of the solution. A maximum adsorption of 5.2 mg/g is obtained at pH value of 3.64. These results suggest that plasma synthesized nanoparticles of NiFe2 O4 have high colloidal stability and can be employed as efficient adsorbents for the removal of humic substances from water sources.